PENGEMBANGAN MEDIA POP UP BOOK UNTUK MENINGKATKAN MINAT BELAJAR PADA MATA PELAJARAN IPA KELAS V SDIT AL-ISTI’AANAH - Yuniar Arifia Maulida; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to increase the interest in learning IPA materni water cycle of grade V SDIT Al-Isti'aanah students in the development of Pop Up Book media. This research uses the type of RnD research with the ADDIE development model. The validity test was carried out by validators who produced 92% for materni expert validation, 90% for linguist validation, and 94% for media expert validation. With the three validator scores, the average was 92%, which showed a very valid category to be tested. The 90% teacher response results prove that the media is very good and practical to use. The results of student responses to Pop Up Bose learning media resulted in 91.85%. The results of the effectiveness of learning interest produce an average percentage of 92% which shows a very effective category. Based on the results of the study, it can be concluded that Pop Up Book media can increase student interest in learning.